Examining karate and football perceptions and their links with athlete engagement and quality of life - Limpo, Teresa; Rödel, Gabriela; Tadrist, Sid (Frontiers in Sports and Active Living, 2022)
The importance of perceptions as determinants of people’s behaviour has been well-established, but little is known about athletes’ perceptions of their sport and the links of these perceptions with other correlates. In this study, we compared karate (n = 51) and football (n = 49) athletes’ perceived benefits and aggressiveness risks from their sports and examined whether these perceptions predicted athletes’ engagement and quality of life (QoL). Participant completed perception measures of karate and football, and engagement and QoL measures. Results showed that karateka perceived more benefits and fewer risks in karate than football, but footballers generally perceived equal benefits and risks in both sports. Both athlete groups perceived similar physical and psychological benefits in their own sport, but deemed physical benefits as prominent outcomes in the other sport. Notably, karateka’s perceived benefits about karate predicted engagement directly and QoL indirectly via vigour. Overall, karate athletes’ perceptions seemed to be relevant to experiencing fulfilment in training and general well-being.